Development of Mathematics Learning Devices Based on Guided Discovery Learning Models and Focusing on Students’ Mathematical Power at SMP Istiqlal Delitua - Julian A. Hartono; Ida Karnasih; Dian Armanto (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
This developmental research aimed to analyze the validity of learning devices, practicality and effectiveness of the devices, as well as student responses to the use of Guided Discovery learning based learning devices that focusing on Mathematical Power. Data collecting was done by using a validation questionnaire with the observation method, a control problem ability test with mathematical power, and student questionnaire responses to guided discovery-based learning tools. Data analysis used qualitative and quantitative descriptive techniques. Testing of research instruments was carried out at SMP Istiqlal Delitua. The results of the analysis of the validity of the equipment showed that the total equipment was declared valid with an average level of validity of 4, 73 very good criteria. The result of the practicality test showed that the device was stated to be very practical with the proportion of practicality level of 89.94%. To test the effectiveness that the learning device was declared effective with the proportion of effectiveness of 86.49%, with Minimum Completeness Criteria achieved 89.29% of students completed, and 10.17% of students not completed. Learning objectives are achieved with the average level of achievement of goals was 88.13%, and students' responses to the feasibility of the devices getting an average total presentation of 94.9% with very good criteria. The results of the test of the ability of mathematical problems obtained an average value of 79.00 with a good predicate and a standard deviation of 9.76, and the test reliability coefficient of 0.5714 in the moderate category. Thus it can be concluded the Guided Discovery Learning device was valid, practical, and effective, and the student's response to the appropriateness of the device was in very good criteria.